PROFESSIONAL DEVELOPMENT OF SENIOR SECONDARY SCHOOL BIOLOGY TEACHERS ON INQUIRY-BASED TEACHING METHOD - Sodan, Anne Ogieriakhi (PEOPLE: International Journal of Social Sciences, 2017)
The paper examined professional development of senior secondary school biology teachers on inquiry-based teaching. To become and remain a competent biology teacher requires a continuous process that starts from pre-service experiences in undergraduate years to the end of a professional career. Science knowledge is constantly changing and expanding its relevance to societal issues therefore, these teachers needs constant opportunities to build their understanding and abilities in the same direction. Consequently, the National Science Education Standards (NSES) presented a vision of learning and teaching science in which students will have the opportunity to become scientifically literate. (NSES)(NRC,1996: 56). In the vision, science teachers are professionally responsible for their own professional development and for the maintenance of their teaching profession, hence this paper. Professional development is a specialized training, formal education or advanced professional learning to offer help to administrators, teachers and other educators improve their professional knowledge, skill and effectiveness in the teaching of biology in the classroom (hidden curriculum, 2014). The paper considered some majors issues that leads to teacher professional development which includes: professional development for biology teachers on inquiry-based teaching, teachers current teaching of biology, concept of inquiry-based teaching, student learning of biology, consensus or standards for professional development programme, impact of professional development programme, researches on professional development programme, challenges of professional development programme, the paper was concluded by stating that coaching and support for teachers at points of implementation should be encouraged, professional development programs should be for a longer period of time more than what is obtainable presently, proper monitoring and evaluation of training received and its implementation among others.